The Profile of Students' Mathematical Communication Ability Viewed from Differences in Learning Outcomes - Solider Rintang Perdana (Universitas Islam Jember, 2019)
Most students assume that mathematics is a complicated subject and has a higher level of difficulty in its delivery. The subject of this study was the tenth grade student of Science at Diponegoro High School in Jember Institution. Based on the problems that exist in this study so that a problem is formulated which is how mathematical communication skills of students who have high learning outcomes, how mathematical communication skills of students who have moderate learning outcomes, and how mathematical communication skills of students who have low learning outcomes. Based on the results of research and discussion it can be concluded that subjects with high learning outcomes have mathematical communication skills at the time of interview giving a minimal model for everyday life. While for the subject of moderate learning outcomes, the subject uses a model / parable in everyday life in order to more easily understand the material that exists. And subjects with low learning outcomes, the subject still cannot find a line that connects the material with the given modeling. Keywoard: mathematical communication skill, learning outcomes